1995
DOI: 10.1111/j.1476-5381.1995.tb15083.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in benzodiazepine‐GABA receptor coupling in an accumbens‐habenula circuit after chronic diazepam treatment

Abstract: 4 In general, the patterns of binding produced by the two different treatment routes were very similar. However, SR 95531 binding was lower in certain hippocampal fields in the i.p. treated animals compared to the rats implanted with silastic capsules. 5 It is concluded that repeated administration of diazepam evokes changes in benzodiazepine and GABA receptor coupling, and to a lesser extent changes in low affinity GABA binding, in certain interrelated brain structures of which an accumbens-habenula circuit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
1
12
1
2
Order By: Relevance
“…While evidence indicates that tolerance develops to the sedative/hypnotic, muscle relaxant and anticonvulsant properties of the benzodiazepines (File 1985;Rosenberg et al 1985), the data demonstrating tolerance to the anxiolytic effects of the benzodiazepines is inconsistent (Margules and Stein 1968;McMillan and Leander 1978;Vellucci and File 1979;Treit 1985a;Brett and Pratt 1995). Our results indicate that low-level continuous exposure to DZ does not induce tolerance to the anxiolytic effects of DZ, as measured by the elevated plusmaze.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…While evidence indicates that tolerance develops to the sedative/hypnotic, muscle relaxant and anticonvulsant properties of the benzodiazepines (File 1985;Rosenberg et al 1985), the data demonstrating tolerance to the anxiolytic effects of the benzodiazepines is inconsistent (Margules and Stein 1968;McMillan and Leander 1978;Vellucci and File 1979;Treit 1985a;Brett and Pratt 1995). Our results indicate that low-level continuous exposure to DZ does not induce tolerance to the anxiolytic effects of DZ, as measured by the elevated plusmaze.…”
Section: Discussioncontrasting
confidence: 46%
“…Using anti-conflict tests, a lack of tolerance to the anxiolytic effect following chronic exposure to a variety of BZs has been shown (Margules and Stein 1968;Cook and Sepinwall 1975;McMillan and Leander 1978). More recent studies using the elevated plus-maze, conditioned defensive burying and the social interaction test have shown that chronic exposure reduces the anxiolytic effects of the BZs tested (Vellucci and File 1979;Stephens and Schneider 1985;Treit 1985b;File 1989aFile , 1989bIshihara et al 1993;Brett and Pratt 1995). These contradictions suggest that procedural differences and the behavioral test used to measure anxiety may affect the demonstration of tolerance following chronic benzodiazepine exposure.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, common structures were activated during withdrawal (Laurie and Pratt, 1993). Despite these brain structures displaying changes in functional activity Pratt, 1989, 1993), they did not exhibit alterations in GABA A receptor binding properties in complementary receptor autoradiography studies (Brett and Pratt, 1995). These studies do not however rule out the possibility that changes in GABA A receptor subunit gene expression may confer alterations in GABA A receptor function in BZ dependence.…”
Section: Introductionmentioning
confidence: 78%
“…Chronic administration of BDZ can produce decreased sensitivity to GABA (Gallager et al 1984) and reduced ability of this amino acid to enhance BDZ binding (Brett and Pratt 1995). Indeed, withdrawal symptoms or spontaneous seizures have been reported to occur in nonepileptic BDZ abusers upon drug discontinuation (Lukas and Griffith 1984).…”
Section: Introductionmentioning
confidence: 99%